Panax notoginseng Saponins Stimulates Neurogenesis and Neurological Restoration After Microsphere-Induced Cerebral Embolism in Rats Partially Via mTOR Signaling - Gao, Jiale; Liu, Jianxun; Yao, Mingjiang; Zhang, Wei; Yang, Bin; Wang, Guangrui (Frontiers in Pharmacology, 2022)
P. Notoginseng Saponins (PNS), the main active component of herbal medicine Panax notoginseng, has been widely used to treat cerebrovascular diseases. It has been acknowledged that PNS exerted protection on nerve injuries induced by ischemic stroke, however, the long-term impacts of PNS on the restoration of neurological defects and neuroregeneration after stroke have not been thoroughly studied and the underlying molecular mechanism of stimulating neurogenesis is difficult to precisely clarify, much more in-depth researches are badly needed. In the present study, cerebral ischemia injury was induced by microsphere embolism (ME) in rats. After 14 days, PNS administration relieved cerebral ischemia injury as evidenced by alleviating neurological deficits and reducing hippocampal pathological damage. What’s more, PNS stimulated hippocampal neurogenesis by promoting cell proliferation, migration and differentiation activity and modulated synaptic plasticity. Increased number of BrdU/Nestin, BrdU/DCX and NeuroD1-positive cells and upregulated synapse-related GAP43, SYP, and PSD95 expression were observed in the hippocampus. We hypothesized that upregulation of brain-derived neurotrophic factor (BDNF) expression and activation of Akt/mTOR/p70S6K signaling after ME could partially underlie the neuroprotective effects of PNS against cerebral ischemia injury. Our findings offer some new viewpoints into the beneficial roles of PNS against ischemic stroke.